Using the balanced scorecard to measure the effectiveness of knowledge management projects in Chinese enterprises. (2018) - Lau, Eric K.W.
A firm's organisational knowledge, which provides its competitive advantage, must be protected, managed, and effectively shared among employees; a function known as knowledge management. This study of Chinese firms, informed by a literature review, examines various knowledge management projects, using the balanced scorecard. The scorecard found significant differences between state-owned and private enterprises, and identified two critical determinants of satisfaction with such projects; how well they supported the financial functions, and the customer-service functions, of the firm.